Alternate side [compact disc, unabridged] : a novel - Quindlen, Anna (Brilliance Audio, 2018)
Nora Nolan always felt she lived a ideal life. But one day tensions in her tight-knit neighborhood--and her seemingly happy marriage--are exposed by an unexpected act of violence.